Prevalence and antibiogram of Staphylococcus aureus isolated from a research laboratory, its transmission and cross contamination to fruits and kitchen utensils - Eden, Vitalis Ronald (2018)
Staphylococcus aureus is an important foodborne pathogen found on the skin and in the nose of a healthy person as normal flora. S. aureus can be acquired and transmitted from contaminated hands to fruits and kitchen utensils. The objectives of this research were to determine the prevalence and antibiogram of S. aureus in microbiology research laboratory, transmission and its cross contamination to fruits and kitchen utensils. A total of 320 isolates from nose=80; hands=80; door knobs=80 and table surface=80 were taken from microbiology research laboratory in Petaling Jaya, Selangor were examined for the presence of S. aureus using Most Probable Number method. The strain of S. aureus obtained were used in simulation test using cutting board=15; knife=15; fork=15; table cloth=15; and watermelon=15. The prevalence of S. aureus estimated in microbiology research laboratory was 81.56% whereby 75% before work and 88.12% after work ranged from 3.6 MPN/mL to 140 MPN/mL. In simulation test, it was identified that S. aureus can be transmitted via contaminated hands to fruits and kitchen utensils during food preparation whereby about 65.3% of S. aureus obtained from 75 isolates and watermelon recorded the highest load of S. aureus about 86.6%. Meanwhile in antibiogram test, S. aureus were found resistant to oxacillin (85.4%) and gentamicin (74.3%). The Actor Network Theory applied in this study identified that the strains of S. aureus obtained in microbiology research laboratory were able to contaminate the fruits and kitchen utensils during food preparation. Furthermore, Risk Ranger estimated that the risk of acquiring S. aureus were moderate with 4 illnesses predicted per annum scoring about 83/100. Hence, contemporary healthcare strategies must be taken immediately to prevent the transmission of S. aureus in microbiology research laboratory and its cross contamination to fruits and kitchen utensils.